Reckoning the Improvement of Community Independence at Community Learning Activity Center in Indonesia - Akmala Hadita (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Community Learning Activity Center, or PKBM, is one of the institutions that contribute to the review and development of community-based education. Community-based education attempts to understand and identify needs and how to meet them while considering the community’s capabilities. As such, this study seeks to explain the community activity center’s role as a centre for community empowerment to increase community independence. The method used in this study is a literature study with the obtained data from articles published in national journals. The results show that many PKBMs are not optimal for educational activities due to various problems. Appropriate empowerment strategies are needed to create an independent community more quickly. Besides that, it is also necessary to have competent PKBM management with technical capabilities in education and community empowerment and innovative empowerment programs so that the implementation can be successful.